In vitro studies on the selective cytotoxic effect of luminescent Ru(ii)-p-cymene complexes of imidazo-pyridine and imidazo quinoline ligands. Issue 45 (1st November 2022) - Selvam, Pravinkumar; De, Sourav; Paira, Priyankar; Kumar, S. K. Ashok; Kumar R, Selva; Moorthy, Anbalagan; Ghosh, Arjita; Kuo, Yung-Chih; Banerjee, Subhasis; Jenifer, Shantha Kumar
Abstract : In recent years, Ru(ii ) complexes have gained high importance in medicinal chemistry due to their significant anti-cancer activities, which are directly related to their DNA binding ability. Abstract : In recent years, Ru(ii ) complexes have gained high importance in medicinal chemistry due to their significant anti-cancer activities, which are directly related to their DNA binding ability. In this report, the chemistry and cytotoxicity of two new Ru(ii ) complexes containing imidazole pyridine (Ru-1 ) and imidazole quinoline (Ru-2 ) have been studied. The prepared compounds were characterized using infrared (IR), nuclear magnetic resonance (NMR), mass spectrometry (MS), isothermal titration calorimetry (ITC), UV-Vis, and fluorescence spectral techniques. The structural analyses show that the Ru(ii ) complexes exhibit a 'piano stool' coordination geometry and they are composed of one bound arene, two sigma bonded benzil nitrogen atoms, and labile chlorine linked to Ru(ii ). The photo-physical properties of these complexes were examined, and they exhibit absorption peaks at 260 nm and 380 nm, which are due to the involvement of intra-ligand charge transitions (ILCT) and metal-to-ligand charge transitions (MLCT), respectively. The binding process of the Ru(ii ) complexes with DNA and BSA is non-covalent in nature and the binding constants of Ru-1 and Ru-2 complexes with DNA and BSA were found to be 1 × 10 5 M −1 and 1 × 10 3 M −1, respectively. In the presence of the Ru(ii ) complexes, ethidium bromide (EtBr) is competitively displaced from DNA by intercalation of the Ru(ii ) complexes in DNA and it is well corroborated by viscosity and in silico studies. Both the ligands and Ru(ii ) complexes were carefully investigated in vitro for cytotoxicity against HeLa, MCF-7, and MDA-MB-231 cells. Surprisingly, both Ru(ii ) complexes exhibit superior cytotoxicity to cisplatin with a low LD50 value against the examined cancer cells. Besides, an insignificant effect on HEK normal cells (LD50 > 140 μM) was observed.